IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA BERBASIS CANVA: TRANSFORMASI TEKS PROSEDUR MENJADI INFOGRAFIK PADA SISWA KELAS IX SMP - Tuti Mayasuci; Eko Suroso (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT This study aims to describe the implementation of Canva-based Indonesian language learning in transforming procedural texts into infographics for ninth-grade students at SMP Negeri 2 Karangpucung, to identify the challenges faced by teachers and students, and to analyze students’ responses to the learning process. Procedural text learning, which has traditionally focused on linguistic structure, is often considered less engaging; therefore, learning innovation that integrates digital technology and 21st-century skills is required. This study employed a descriptive qualitative method with ninth-grade students as the research subjects. The research stages included lesson planning using Canva, implementation of learning activities involving the transformation of procedural texts into infographic formats, and evaluation through reflection and analysis of students’ responses. Data were collected through classroom observations, interviews with teachers and students, and questionnaires to assess students’ perceptions. The results indicate that the use of Canva increased student engagement, creativity, and the ability to present information visually. The challenges encountered included limited access to digital devices and varying levels of students’ digital literacy. Overall, students showed positive responses, perceiving the learning activities as interesting, easy to understand, and helpful in improving their comprehension of procedural texts. In conclusion, Canva-based learning is an effective and innovative alternative for teaching procedural texts in Indonesian language classes. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran Bahasa Indonesia berbasis Canva dalam mentransformasikan teks prosedur menjadi infografik pada siswa kelas IX SMP Negeri 2 Karangpucung, mengidentifikasi kendala yang dihadapi guru dan siswa, serta menganalisis respons siswa terhadap pembelajaran tersebut. Pembelajaran teks prosedur yang selama ini cenderung berorientasi pada struktur kebahasaan dinilai kurang menarik, sehingga diperlukan inovasi pembelajaran yang mengintegrasikan teknologi digital dan penguatan keterampilan abad ke-21. Penelitian ini menggunakan metode kualitatif deskriptif dengan subjek siswa kelas IX. Tahapan penelitian meliputi perencanaan pembelajaran berbasis Canva, pelaksanaan pembelajaran transformasi teks prosedur ke bentuk infografik, serta evaluasi melalui refleksi dan pengumpulan respons siswa. Teknik pengumpulan data dilakukan melalui observasi aktivitas pembelajaran, wawancara dengan guru dan siswa, serta penyebaran angket untuk mengetahui respons siswa. Hasil penelitian menunjukkan bahwa penggunaan Canva mampu meningkatkan keterlibatan siswa, kreativitas, serta kemampuan menyajikan informasi secara visual. Kendala yang ditemukan meliputi keterbatasan akses perangkat dan variasi kemampuan literasi digital siswa. Secara umum, siswa memberikan respons positif terhadap pembelajaran ini karena dianggap menarik, mudah dipahami, dan membantu pemahaman materi. Simpulan penelitian ini menunjukkan bahwa pembelajaran berbasis Canva efektif sebagai alternatif inovatif dalam pembelajaran teks prosedur.